Systematic Design and Implementation of Distributed Controllers in Industrial Automation - Vyatkin, V.; Hirsch, M.; Hanisch, H.-M. (2006 IEEE Conference on Emerging Technologies and Factory Automation, 2006)
This paper discusses systematic approaches to the design of distributed controllers in industrial automation systems. Several design approaches are compared that lead to the distributed control of manufacturing machines and their parts. In particular, a decentralized control method is introduced that does not require a master controller. The implementation frameworks of IEC 61131-3 and IEC 61499 are checked on their fitness to the distributed control. A migration method from a PLC-based control to IEC 61499 is illustrated. A layered architecture for distributed controllers is introduced and tested on examples.